Alimentos para o mercado institucional da alimentação escolar: um estudo a partir das chamadas públicas na região do Arquipélago do Marajó - MARTINS, Jamilly Lopes (2023)
This study aims to analyze the sideview of Marajó’s public calls, identifying the major impediments in the performance of the National Schools Meals Program. It had been analyzed 13 notices of public calls wich were avaliable on oficial websites. Analyzing the transfers and the resources applications for familyfarming as well as the form of the nourishment which were found. With the aid of a checklist, it was found disagreements about the notices. Among the majority of the obitained results, stood out the inexistence of the delivery place and time schedules, the description of the notices’ opening period, the abstance of specifications about the price, obstance of delievry frequency description, the request of expiration dates, of sample testing and the foodstuffs replecement references. The sideviews of the found foods were suitable according to PNAE’S (Law 11.947/2002) specifications. It was concluded that the acquired data was satisfactory in its most part. One of the goals to be achieved is the qualification of the purchasing sector from the Executive Instituitions, aiming for the improviment of the notices elaboration, to get a fairer purchasing and transparent process.